The influence of digital marketing on purchasing decision for fruit plant seedlings in Bali Province - Yudhari, I Dewa Ayu Sri; Anggreni, I Gusti Ayu Agung Lies (International journal of economic perspectives, 2024)
Entrepreneurs involved in fruit plant seedling business in Bali Province utilize various digital marketing platforms. This study aims to examine the most widely used digital marketing platform in the purchase of fruit plant seedlings in Bali. Additionally, to analyze the influence of digital marketing in terms of convenience, content, response, security, and trust on the purchasing decisions of fruit plant seedlings. The research was conducted in Bali Province using both online and offline media. The sampling technique used was purposive sampling. The data analysis method involved qualitative descriptive analysis and Structural Equation Modelling-Partial Least Square (SEM-PLS). The results revealed that the most widely used digital marketing platform among fruit plant seedling entrepreneurs in Bali Province is a social media, WhatsApp. Factors such as convenience, responsiveness, and trust significantly influence purchasing decisions in the digital marketing of fruit plant seed business products in Bali Province. However, content and security have no significant effect. Fruit plant seedling businesses that utilize digital marketing should pay more attention to aspects of convenience, response, and customer trust to enhance purchasing decisions. This research provides insights the use of digital marketing and the factors influencing purchasing decisions of the fruit plant seedling business in Bali Province.